Nonsteroidal anti‐inflammatory drugs enhance IgE‐mediated activation of human basophils in patients with food anaphylaxis dependent on and independent of nonsteroidal anti‐inflammatory drugs. Issue 8 (7th May 2016) - Pascal, M.; Muñoz‐Cano, R.; Milà, J.; Sanz, M. L.; Diaz‐Perales, A.; Sánchez‐López, J.; García‐Moral, A.; Juan, M.; Valero, A.; Yagüe, J.; Picado, C.; Bartra, J.
Summary: Background: Nonsteroidal anti‐inflammatory drugs (NSAIDs) act as cofactors worsening the allergic reactions induced by food allergens. Aim: The aim of this study was to evaluate the effect of both lysine acetylsalicylate (L‐ASA) (non‐selective cyclooxygenase (COX) inhibitor) and valdecoxib (selective COX‐2 inhibitor) in basophils activated by peach lipid transfer protein (Pru p 3) in patients with food‐dependent NSAID‐induced anaphylaxis (FDNIA). Methods: Twenty Pru p 3‐allergic patients with FDNIA group, eleven peach anaphylaxis not exacerbated by NSAIDs (no‐NSAID group) and 5 healthy volunteers were recruited. Basophil activation (BA) was measured as expression of CD63 (Flow 2 CAST ™ ; Bühlmann ® ), after stimulation with Pru p 3, both alone and in combination with L‐ASA (1.13, 3.38 and 6.78 mm ) or valdecoxib (0.87, 7.8 and 31.25 μm ). Results: Basophils from no‐NSAID group were significantly more reactive and sensitive to Pru p 3 than those from the FDNIA group. In both groups, an increase in BA was observed when basophils were exposed to Pru p 3 and L‐ASA. In the FDNIA group, valdecoxib partially terminates the BA induced by Pru p 3, whereas in the no‐NSAID group, a dual effect was observed depending on the concentration tested. Conclusions: This study indicates that subjects with food‐induced anaphylaxis differ from FDNIA subjects in the higher reactivity and sensitivity of their basophils to allergen challenge. We have shown a direct effect of NSAIDs on basophils using a human model of FDNIA. Our results also suggest that selective COX2 inhibitors might be a safe alternative. BA test may be a useful tool in the study of the pathogenic mechanism of the cofactor phenomenon.